APLIKASI PANDUAN BERWISATA DI YOGYAKARTA BERBASIS MULTIMEDIA - , PRIYO DWI ANGGORO, Faizah, S.Kom., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yogyakarta has a diversity of tourist attractions. Information about tourist attractions that known today, can only be known from the internet or from the promotion about that attractions. The purpose of this research is to make the Guides Traveled Application in Yogyakarta with Multimedia Based as traveled guides for tourist. The steps to make this application is design concepts, data collection, preparation of hardware and software, make the application, testing, repair, and finishing. This application is able to display information about tourist attractions, driving directions, and tour package. Based on the result of the questionnaire can be concluded that the Guides Traveled Application in Yogyakarta with Multimedia Based can facilitated the tourists and 87% of respondents stated that this application deserves to be used as a traveled guides.